While stocks last the live reef food fish trade - Sadovy, Yvonne (Asian Development Bank, 2003)
"This study brings together the work of many researchers to arrive at suggestions for solving the environmental problems caused by the long-running live-fish trade in Southeast Asia. With strong demand coming from mainland China, this trade has caused rampant over-fishing in Asia and consequent damage to outside subsistence or commercial fisheries. This work discusses the role of regional organizations in regulating the trade as well as ways to decrease nontarget fish mortality in an industry that often employs cyanide solution as a fishing tool." --Provided by publisher